2009
DOI: 10.4049/jimmunol.182.2.934
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous 4-1BB Ligand Plays a Critical Role in Protection from Influenza-Induced Disease

Abstract: A critical issue during severe respiratory infection is whether it is the virus or the host response that does the most damage. In this study, we show that endogenous 4-1BBL plays a critical role in protecting mice from severe effects of influenza disease. During mild respiratory influenza infection in which virus is rapidly cleared, the inducible costimulatory receptor 4-1BB is only transiently induced on lung T cells and 4-1BB ligand (4-1BBL) is completely dispensable for the initial CD8 T cell response and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(40 citation statements)
references
References 70 publications
5
35
0
Order By: Relevance
“…Transient 4-1BB expression likely translated to a brief period of signaling from anti-4-1BB to augment clonal division in the effector cells, but the necessary pro-survival signals may not have been induced that result from extended 4-1BB signaling and that might be needed to allow greater accumulation of memory cells. Our findings are reminiscent of a prior study (Lin et al, 2009) that showed that 4-1BB expression on CD8 T cells was prolonged with respiratory tract infection of a virulent influenza virus compared to a milder influenza virus. This also correlated with a requirement for 4-1BB in the T cell response to the former, whereas 4-1BB was dispensable for the response to the less virulent strain.Similarly, anti-4-1BB was previously shown to enhance primary T cell responses to influenza virus delivered by the non-productive i.p.…”
Section: Discussionsupporting
confidence: 85%
“…Transient 4-1BB expression likely translated to a brief period of signaling from anti-4-1BB to augment clonal division in the effector cells, but the necessary pro-survival signals may not have been induced that result from extended 4-1BB signaling and that might be needed to allow greater accumulation of memory cells. Our findings are reminiscent of a prior study (Lin et al, 2009) that showed that 4-1BB expression on CD8 T cells was prolonged with respiratory tract infection of a virulent influenza virus compared to a milder influenza virus. This also correlated with a requirement for 4-1BB in the T cell response to the former, whereas 4-1BB was dispensable for the response to the less virulent strain.Similarly, anti-4-1BB was previously shown to enhance primary T cell responses to influenza virus delivered by the non-productive i.p.…”
Section: Discussionsupporting
confidence: 85%
“…Interestingly, lack of GITR did not appear to change the percentage of CD8+ T cells that became IFNγ+ [21••]. This finding was similar to a previous one by the same group demonstrating reduced survival of 4-1BB−/− mice challenged with the PR8 strain [22•]. Thus, although GITR and 4-1BB may be similar, they seem to serve non-redundant roles.…”
Section: Role In Immune Activationsupporting
confidence: 79%
“…Several other less obvious approaches have also been taken to limit inflammation or control immune responses in the lung in response to infection. For example, one group used 4-1BB ligand (4-1BBL) to protect from lung injury caused by influenza infection in the lung 79 . 4-1BBL binds to 4-1BB (CD137), a member of the TNF receptor family expressed on activated T cells that is rapidly up-regulated on T cells following viral infection.…”
Section: Gene Therapy For Ali/ardsmentioning
confidence: 99%